2013
DOI: 10.5694/mja13.10331
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in Victoria: are we making progress?

Abstract: Opportunities to improve patient management included increasing the proportion with a pathologically confirmed diagnosis and greater use of postsurgical adjuvant chemotherapy. A high proportion of patients received no treatment, with underuse of chemotherapy and radiotherapy. Critically, the low rate of case discussions at MDMs needs to increase. However, effective strategies are required to identify cases early, as over two-thirds currently present with incurable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 19 publications
5
78
3
Order By: Relevance
“…Unlike others5 6 but consistent with some NSW studies,10 33 though not all,34 we did not find that socioeconomic status affected the hazard of dying from lung cancer. We also found, as have other Australian9–11 31 and UK studies,7 that there were higher hazards of death in patients with any comorbidity,8 those without histological confirmation35 and patients who were admitted through the emergency department 36…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unlike others5 6 but consistent with some NSW studies,10 33 though not all,34 we did not find that socioeconomic status affected the hazard of dying from lung cancer. We also found, as have other Australian9–11 31 and UK studies,7 that there were higher hazards of death in patients with any comorbidity,8 those without histological confirmation35 and patients who were admitted through the emergency department 36…”
Section: Discussionsupporting
confidence: 86%
“…A recent lung cancer audit in Victoria, Australia, found that multidisciplinary team management of lung cancer patients, which is most likely to be available in specialist centres, was an independent predictor of receiving guideline based treatment and of a lower hazard of death 31. Specialised facilities and practices are less likely to be available in general hospitals, which tend to be outer urban or rural and to serve smaller, less dense populations 32…”
Section: Discussionmentioning
confidence: 99%
“…A US study among 500000 people found a 30% higher incidence of lung cancer in women never smokers compared with men never smokers 19. An Australian study found the proportion of patients with lung cancer who had never smoked was approximately 18% in women and 3% of men 20. The reasons for this sex difference are not clear, but women may have increased exposure to environmental tobacco smoke21 or other environmental carcinogens such as indoor air pollution22 or sex-related differences in the metabolism of environmental carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…It is the fourth most common neoplasm in both men and women, and in 2014 more than 11 000 people were diagnosed with lung cancer in Australia 1 . The 5‐year survival rate is 14%; 1 the median survival time for patients with non‐small cell lung cancer (NSCLC) is 6.9 months, and for small cell lung cancer (SCLC) it is 7.2 months 2 …”
mentioning
confidence: 99%